Serological evidence of anaplasma spp. in small ruminants from Venezuela using recombinant msp5 in immunoenzymatic assay - Tavares Marques, Lucinda; Núñez, Cristina; Rey Valeirón, Catalina; Reyna Bello, Armando (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Anaplasma marginale causes a disease in cattle characterized by fever, anemia and decrease in milk and meat production. Small ruminants do not show signs of disease when infected, but it has been suggested they could act as reservoirs. Goat and sheep breeding is socially and economically important in arid and semi-arid areas in Venezuela, and these species often share space and food with cattle. The aim of this work was to detect antibodies against Anaplasma spp. in Venezuelan goat and sheep flocks. To accomplish this goal, an indirect ELISA using recombinant MSP5 as antigen of A. marginale was performed. Sera obtained from experimental infection in goat and a hyperimmune sheep serum were used as positive controls. Blood sera were obtained from 45 sheep and 48 goats located in Guárico State, an endemic area to bovine anaplasmosis. After standardization of assay for each species, 80.46% of the sheep and 59.25% of the goat sera showed to have antibodies against MSP5. No signs of clinical disease were detected in sampled animals. These results suggest that small ruminants could harbour A. marginale and consequently may be reservoirs for neighbouring cattle if appropriate vectors are present. The development of clinical diseases caused by A. marginale under stress situations and the existence of other Anaplasma species (e.g. A. ovis) in small ruminants should also be investigated.